Chip/Ldb1 interacts with Tailup/islet1 to regulate cardiac gene expression in Drosophila. Issue 4 (3rd April 2017) - Werner, Kathrin; Donow, Cornelia; Pandur, Petra
Abstract: The LIM‐homeodomain transcription factor Tailup (Tup) is a component of the complex cardiac transcriptional network governing specification and differentiation of cardiac cells in Drosophila . LIM‐domain containing factors are known to interact with the adaptor molecule Chip/Ldb1 to form higher order protein complexes to regulate gene expression thereby determining a cell's developmental fate. However, with respect to Drosophila heart development, it has not been investigated yet, whether Chip and tup interact to regulate the generation of different cardiac cell types. Here we show that Chip is required for normal heart development and that it interacts with tup in this context. Particularly the number of Odd skipped‐expressing pericardial cells depends on balanced amounts of Chip and Tup. Data from luciferase assays using Hand ‐ and even‐skipped reporter constructs in Drosophila S2 cells indicate that Chip and Tup act as a tetrameric complex on the regulatory regions of Hand and even‐skipped ( eve ). Finally we have identified and verified five Tup binding sites in the eve mesodermal enhancer, which adds Tup as novel factor to directly regulate eve expression. Taken together this study provides novel findings regarding cardiac gene expression regulation in Drosophila .